Relationship Between Quality Indicators and Student Satisfaction in Higher Education - Ahmad, Md. Fauzi; Mohd Razaki , Nur Aesyah; Ahmad, Ahmad Nur Aizat (Research in Management of Technology and Business, 2021)
Higher education institutions provide students relevant knowledge and skills for students’ adaptability to workforce. Quality indicators are measurement tools to classify and analyze students’ satisfaction data based on the service quality experiences. The current issues are inequality of service quality among universities in Malaysia. Low students’ satisfaction contribute to lower students’ performance and hardly to fit into current employment market. This research focuses on the relationship between quality indicators of service quality provided by UTHM and students’ satisfaction. A previous study found that high percentage of students voted for UTHM services quality improvement. Therefore, the level of customers’ satisfaction in UTHM is an issue that need to be improved. Collection of the data was done by distributing questionnaires to 100 respondents from undergraduates of fourth year students among six faculties. The sampling techniques was stratified sampling method. The result showed that the extent level of quality indicators and student’s satisfaction in UTHM are mostly at high levels. Each of the quality indicators has positively impact on students’ satisfaction. This study was to evaluate the current level of service quality in UTHM in students’ viewpoint for future improvement in providing a better learning environment.